Determination of the cost-benefit efficient interval for sponge city construction by a multi-objective optimization model - Liang, Changmei; Zhang, Xiang; Liu, Jie; Liu, Luguang; Tao, Shiyong (Frontiers in Environmental Science, 2023)
The cost-benefit is a key factor when selecting an appropriate sponge city construction scheme To comprehensively analysis the cost-benefit of sponge city construction, this paper established a multi-objective simulation optimization framework of sponge city construction which considered minimization of runoff control rate, pollutant control rate and life-cycle cost Non-dominated sorting genetic algorithm (NSGA-II) was successfully coupled to SWMM to complete the simulation-optimization process.. A case study in Xining, China, was conducted to demonstrate the proposed framework. The results of this research suggested that (1) different sponge city construction schemes lead to different runoff control rates and pollutant control rates although under the same investment; (2) the runoff control rate and pollutant control rate (TSS) decreased with the increase of the rainfall return period, while the cost of sponge city construction increased with the increase of rainfall return period. Furthermore, for T=2-year, the sponge facility exhibited the most stable control effect on runoff and pollutants among the three different return periods (T=2-year, 5-year, 10-year); (3) sponge city construction exhibited a "cost-benefit" efficient interval. for T=2-year, the cost-benefit high efficiency interval of sponge city construction is calculated between 1.2 billion and 1.8 billion; for T=5-year, the interval is between 1.2 billion and 1.8 billion, while for T=10-year, the interval is between 1.3 billion and 2.1 billion. The above observations provide reference for reasonable and effective sponge city construction in Xining, China.